2015
DOI: 10.1007/s10764-015-9842-4
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Socialization of Chimpanzees (Pan troglodytes) Used for Entertainment and as Pets: An 8-Year Study at Fundació Mona

Abstract: Abstracts Primates are at times used as performers in circuses, advertisements, films, and as pets. Most of these animals are socially isolated from their peers. They exhibit behavioral problems and lack important skills for living in a group environment. One of the main challenges primate rescue centers face is creating groups to socialize rescued individuals and promote the development of species-typical behaviors. We monitored a group of 15 chimpanzees (Pan troglodytes) housed at Fundació Mona, a primate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 58 publications
(58 reference statements)
2
31
0
Order By: Relevance
“…For example, Freeman and Ross [4] found that chimpanzees, living in accredited zoos and sanctuaries, who had more exposure to humans as infants exhibited less social grooming and sexual behaviours than chimpanzees with more conspecific exposure during infancy. Likewise, Llorente and colleagues [10] found that chimpanzees living in a sanctuary who were younger at the onset of rehabilitation spent more time with social play and affiliative behaviours, less time inactive, and reached higher levels of behavioural and social competence than individuals who started their rehabilitation at an older age. Furthermore, former pet and entertainment chimpanzees, living in accredited zoos and sanctuaries, who were mainly exposed to humans in infancy showed lower levels of extraversion and exhibited deficiencies in social bonding [38].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Freeman and Ross [4] found that chimpanzees, living in accredited zoos and sanctuaries, who had more exposure to humans as infants exhibited less social grooming and sexual behaviours than chimpanzees with more conspecific exposure during infancy. Likewise, Llorente and colleagues [10] found that chimpanzees living in a sanctuary who were younger at the onset of rehabilitation spent more time with social play and affiliative behaviours, less time inactive, and reached higher levels of behavioural and social competence than individuals who started their rehabilitation at an older age. Furthermore, former pet and entertainment chimpanzees, living in accredited zoos and sanctuaries, who were mainly exposed to humans in infancy showed lower levels of extraversion and exhibited deficiencies in social bonding [38].…”
Section: Introductionmentioning
confidence: 98%
“…Adverse experiences in early infancy affect the behaviour as well as the physical and mental health of human [1][2][3] and non-human primates [4,5] in the long term [6][7][8][9]. This applies to individual as well as social behaviour [10]. Wild infant chimpanzees spend their first two to five years of life either attached to or in close proximity to their mothers [11][12][13], and develop their social skills by interacting with their mother and other members of their group [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, due to the genetic, biological, and psychological proximity, nonhuman primates have been preferred as a comparative animal model to understand what triggers early life stress products in humans (Gilmer & McKinney, ; Nelson & Winslow, ). Decades of studies revealed that early impoverished, neglected, and abused primates show long‐term effects on cortical organization (Bogart, Bennett, Schapiro, Reamer, & Hopkins, ), cognitive deficits (Davenport, Rogers, & Rumbaugh, ), greater expression of abnormal and stereotyped behaviors (Birkett & Newton‐Fisher, ; Kalcher‐Sommersguter, Franz‐Schaider, Preuschoft, & Crailsheim, ; Latham & Mason, ), less social and sexual behaviors (Freeman & Ross, ; Kalcher‐Sommersguter et al, ; Llorente, Riba, Ballesta, Feliu, & Rostán, ), attachment disorders (van Ijzendoorn, Bard, Bakermans‐Kranenburg, & Ivan, ), anxiety (Botero, Macdonald, & Miller, ), increased inactivity (Llorente et al, ), neophobia (Ueno & Matsuzawa, ), and higher stress sensitivity (Reimers, Schwarzenberger, & Preuschoft, ), than mother‐reared and normal developed chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…We focused not only on abnormal and stress-related behaviours often used to gauge welfare (e.g., Llorente et al, 2015;Pomerantz and Terkel, 2009) but also on a potential positive welfare indicator, play, in line with the increased interest in welfare science paradigms that include positive outcomes (Mellor et al, 2009;Mellor, 2015). Play has been proposed as one of the most promising positive welfare indicators because it is more likely to be performed when animals are experiencing positive affective states, the behaviour is linked with positive emotions, and it is reduced when animals are faced with poor conditions (Boissy et al, 2007;Held anď Spinka, 2011).…”
Section: Introductionmentioning
confidence: 99%